Effect of national-level field hockey on physical fitness and body composition parameters in Turkish females - Ucan, Y. (The Sport Journal, 2015)
To be successful in field sports such as soccer, rugby, football and hockey, players need to be enhancing some bio-motor abilities like endurance, strength, speed and flexibility. The purpose of this study was to investigate the effects of national-level field hockey on physical fitness and body-composition parameters in Turkish females. Twenty-four female subjects (12 non-sporting healthy controls aged 19 to 22, 12 elite, national level field hockey players aged 18 to 21) participated in this study. Body composition, 30-meter sprint, leg power, handgrip strength, posture balance were measured. At the end of measurements, there was a significant differences in body-fat percentage (p < 0.014), fat mass (p < 0.044), speed (p < 0.000), leg power (p < 0.006), grip strength (p < 0.022), but no significant differences in fat-free mass (p > 0.442) and fall index (p > 0.258) were observed between hockey players and non-sporting controls. Results suggest that regular participation to hockey training programs improves body composition, speed, and lower- and upper-extremity strength, with no effect on fat-free mass and posture balance in young females. Additional studies may identify effects of field hockey training on physical fitness and body composition in males and different age groups.